Preparedness School Citizens of State Elementary School in Facing Flood through Digital Literation - Prananingrum, E Nugrahaeni; Setiawan, Cahyadi; Nikita Theresia Afdan; Shalsa Billa; Muhammad Wahyu Wardana (MIMBAR PGSD Undiksha, 2023)
Literation serves as an important factor in education and learning process at school so that the community obtains ability in surviving at any disaster risks. This research aims to analyze the preparedness of school citizens of State Elementary School in facing Flood by Digital Literation. This research used a qualitative approach with data collection technique was used to observation, documentation and in-depth interview with school citizens. The subject of this study was school citizen of state elementary school 05 Bidara Cina included a student class 4th grade and 5th grade, teacher, principle, and vice principle. This research using primer data through LIPI/UNSECO, and secondary data was collecting the information. Results of this study found that the school has not yet used social media as a material to disclose information of knowledge on flood. Integrated information about disaster in this school still restrictiveness through Whatsapp. Based on interview results with headmaster, vice headmaster, teachers and 3 students still lack of literacy digital. It can be showed that school did not provide media information about disaster in their school or through school website. It is important to enhance preparedness of digital literacy in prone area so that school   are able to take advantage of digital media to get informatioan about flood disaster and also quickly inform school community to prepared for disaster.